Komentar Netizen dan Normalisasi Bullying di Tiktok - Ifit Novita Sari; Syafrianza Maulana; Badiatul Azizah; Ajda Amalia Amalia Putri Nasution; Safira Ramadani Mahfud (Badan Pengembangan dan Pembinaan Bahasa, 2025)
The development of social media has changed the way individuals communicate, but it has also given rise to the phenomenon of cyberbullying that is becoming more widespread, especially on platforms like TikTok. Negative comments and hate speech from netizens are often normalized, reflecting the failure to internalize the values of character education in digital interactions. The purpose of this study is to analyze how netizens' comments on TikTok contribute to the normalization of bullying behavior and examine the implications of this phenomenon on the effectiveness of character education. This study uses a qualitative approach with the Critical Discourse Analysis (CDA) method on comments uploaded on several teenage TikTok accounts with a high number of followers. Data were collected through purposive sampling techniques and analyzed with a thematic approach to identify bullying narrative patterns and factors that influenced them. The results showed that bullying comments were often supported or ignored by other users, creating a permissive digital environment for negative behavior. Anonymity factors, viral trends, and low digital literacy contribute to the high rate of bullying comments on TikTok. The normalization of bullying in netizens' comments on TikTok shows the weak internalization of character values in digital interactions. These findings indicate the need for a more adaptive and digital-based character education strategy to suppress the culture of cyberbullying. Keywords: bullying on TikTok, character education, digital interaction, netizens' comments, normalization of cyberbullying Abstrak Perkembangan media sosial telah mengubah cara individu berkomunikasi, namun juga memunculkan fenomena cyberbullying yang semakin meluas, terutama di platform seperti TikTok. Komentar negatif dan ujaran kebencian dari netizen sering kali dinormalisasi, sehingga mencerminkan kegagalan internalisasi nilai-nilai pendidikan karakter dalam interaksi digital. Tujuan penelitian ini untuk menganalisis bagaimana komentar netizen di TikTok berkontribusi terhadap normalisasi perilaku bullying serta mengkaji implikasi fenomena ini terhadap efektivitas pendidikan karakter. Penelitian ini menggunakan pendekatan kualitatif dengan metode analisis wacana kritis Critical Discourse Analysis (CDA) pada komentar yang diunggah di beberapa akun TikTok remaja dengan jumlah pengikut yang tinggi. Data dikumpulkan melalui teknik purposive sampling dan dianalisis dengan pendekatan tematik untuk mengidentifikasi pola narasi bullying serta faktor yang memengaruhinya. Hasil penelitian menunjukkan bahwa komentar bernada bullying sering kali mendapatkan dukungan atau diabaikan oleh pengguna lain, sehingga menciptakan lingkungan digital yang permisif terhadap perilaku negatif. Faktor anonimitas, tren viral, dan rendahnya literasi digital berkontribusi terhadap tingginya tingkat komentar bullying di TikTok. Normalisasi bullying dalam komentar netizen di TikTok menunjukkan lemahnya internalisasi nilai karakter dalam interaksi digital. Temuan ini mengindikasikan perlunya strategi pendidikan karakter yang lebih adaptif dan berbasis digital untuk menekan budaya cyberbullying.